Diversity of macrofungi and exploitation of edible mushroom resources in the National Park "Appennino Lucano, Val D'Agri, Lagonegrese" (Italy). (2nd September 2016) - Venturella, G.; Gargano, M. L.; Compagno, R.; La Rosa, A.; Polemis, E.; Zervakis, G. I.
Abstract : An investigation on the macrofungal diversity of the National Park "Appennino Lucano, Val D'Agri, Lagonegrese" (Basilicata, southern Italy) was carried out, together with an evaluation of wild edible mushrooms in agro-forest ecosystems and their possible exploitation as a new source of food and revenue in rural and under-developed areas of this region. An unpublished list of 249 mushroom taxa (229 Basidiomycota and 20 Ascomycota ), mostly belonging to the genera Tricholoma, Tuber, Russula, Amanita, Boletus, Lactarius, Mycena, Agaricus, Clitocybe and Hygrophorus, growing in this important natural area is provided together with ecological characterization of the recorded specimens. Inonotus obliquus is a new record for Basilicata, while Mycena bresadolana is reported for the first time from southern Italy. The presence of Amaurodon mustialaënsis, an extremely rare species of the northern hemisphere reported for the first time on white fir, is noteworthy. Among the previous findings, 116 species of edible mushrooms are presented and discussed in view of their relative abundance and edibility.